50.0k views
5 votes
Please please please help!! ASAP

Please please please help!! ASAP-example-1
User Woei
by
5.7k points

1 Answer

1 vote

I prefer to use a midpoint formula that deals with both coordinates at once. For points A and B, their midpoint (M) is

... M = (A + B)/2

We can solve this for B by multiplying by 2 and subtracing A.

... 2M = A + B

... 2M - A = B

For your midpoint M(0, -10) and your endpoint A(-4, -5), the other endpoint will be

... B = 2(0, -10) - (-4, -5) = (2·0 -(-4), 2·(-10) -(-5))

... = (4, -15)

User Bharatsing Parmar
by
5.3k points